Intradermal application of tranexamic acid (TA) as treatment of melasma in the out-patients department of a public sector hospital: a pilot study - Mehmood, Muzna; Ali, Muhammad; Saleem, Muhammad Amer; Asghar, Sikandar; Hussain, Muhammad Tanveer; Mehmood, Asim (Journal of the Pakistan Medical Association, 2022)
The effect of intradermal TA on melasma was evaluated as a possible treatment modality on all of the 11 patients (fitting the inclusion criteria) presenting in the out-patient department of the Benazir Bhutto Hospital, Rawalpindi during Sep 2019 to Mar 2020. Their pre- and post-interventional results were evaluated after being injected with 4 mg/ml of TA on the lesions once weekly for 6 weeks, using Wilcoxon signed rank test in SPSS v 24. The average duration of melasma in our patients was 25.3 ± 7.6 in months. The mean modified MASI score rating was 12.2 (2.3) and 5.1 (1.4) before and after intervention with intradermal TA respectively. The largest difference obtained in the mMASI scores of the patients was 10.8. TA has a distinctive effect as a treatment modality for melasma, as it is easily employable with very few side effects. Keywords: Melasma, Tranexamic acid, TA, intradermal TA, mMASI.